SITUATION OF WAR-AFFECTED PEOPLE IN POST-CONFLICT SOMALIA AND THEIR NEED FOR ISLAMIC MICROFINANCE SERVICES: A QUALITATIVE SURVEY - Mohamed Abdikarim Ali; Prof. Dr. Rusni Hassan; Assoc. Prof. Dr. Salina Hj Kassim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2019)
This paper aims identify the situation of the poor and war-affected people in post-conflict Somalia and highlight the potential roles microfinance in alleviating poverty and enhancing their lives in the country. This paper also aims to establish foundational argument for developing microfinance best practices to provide affordable, accessible and efficient Islamic microfinance services the specific context of post-conflict Somalia. The paper adopts qualitative research approach using phenomenological method to investigate the situation of war-affected people in post-conflict Somalia and how the introduction of suitable microfinance services can be the help solve the poverty and sufferings of these people in many ways. The study collected primary data through conducting interviews with fifteen key informants in the microfinance sector of the country, such as lead managers to the institutions offering microfinance services, the regulators of the central bank of Somalia CBS and other government officials including the current Deputy Minister of Finance in Somalia to gain holistic understanding on the issues at stake. It is found that the short experience of microfinance in Somalia faces several issues and challenges in regard to reaching for the ultra-poor in the country especially the war-affected people such as IDPs and returning refugees. The paper also found that microfinance can be a viable intervention mechanism to enhance the standard living of these disadvantaged people that was harmed by the long civil war.